PERILAKU KERJA INOVATIF SEBAGAI MEDIASI PENGARUH FAKTOR INDIVIDU DAN ORGANISASI TERHADAP KINERJA KARYAWAN UMKM - Fatkhurahman Fatkhurahman; Aznuriyandi Aznuriyandi; Safrul Rajab (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the influence of individual and organizational factors on the performance of MSME employees with innovative work behavior as a mediating variable. The study was conducted on MSME actors and employees in Pekanbaru City operating in the creative industry, food and beverage, and trade sectors. The research approach used was quantitative with a survey method. Data were collected through a structured questionnaire from 290 respondents selected using a purposive sampling technique. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) using the SmartPLS 4 application. The results of the study indicate that individual factors have a positive and significant effect on innovative work behavior, as well as organizational factors which are proven to have a positive and significant effect on innovative work behavior. Furthermore, innovative work behavior has a positive and very significant effect on MSME employee performance. The results of the indirect effect test revealed that innovative work behavior plays a significant mediating variable in the relationship between individual factors and MSME employee performance, as well as between organizational factors and MSME employee performance. These findings confirm that improving MSME performance depends not only on individual characteristics and direct organizational support, but also on employees' ability to generate, promote, and implement innovative ideas. This research provides theoretical contributions to the development of innovative work behavior literature and offers practical implications for MSME managers in designing innovation-based performance improvement strategies.